The impact of ageing on income inequality - Thomas Drosdowski; Britta Stöver; Marc Ingo Wolter (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2015)
The question whether ageing leads to more or less inequality is not easily answered. Different, in part opposed, effects can be identified that are sensible to reactions of private households, the implementation of political measures etc. To get a better idea of the effect of demographic change on the distribution of income in Germany we apply a scenario analysis using the macro-econometric input-output model INFORGE and the socio-economic module DEMOS. Different exogenously given population projections are applied to identify the structural and quantity effect of ageing on inequality of disposable incomes between household groups. In summary, the projected demographic change in Germany is likely to increase income inequality. Main driver is the disproportionate increase in wage income due to labour market shortages. While the quantity effect acts slightly equalising on income inequality, the structural effect definitely raises income inequality.
Keywords: D31; 330; income inequality; ageing; socio-economic modelling; Einkommensverteilung; Alternde Bevölkerung; Privater Haushalt; Rentner; Deutschland